Body posture as a measure of emotional valence in young children: a preregistered validation study - Gerdemann, Stella C.; Vaish, Amrisha; Hepach, Robert (Frontiers in Developmental Psychology, 2025)
IntroductionObjective measures of emotional valence in young children are rare, but recent work has employed motion depth sensor imaging to measure young children's emotional expression via changes in their body posture. This method efficiently captures children's emotional valence, moving beyond self-reports or caregiver reports, and avoiding extensive manual coding, e.g., of children's facial expressions. Moreover, it can be flexibly and non-invasively used in interactive study paradigms, thus offering an advantage over other physiological measures of emotional valence.MethodHere, we discuss the merits of studying body posture in developmental research and showcase its use in six studies. To this end, we provide a comprehensive validation in which we map the measures of children's posture onto the constructs of emotional valence and arousal. Using body posture data aggregated from six studies (N = 466; Mage = 5.08; range: 2 years, 5 months to 6 years, 2 months; 220 girls), coders rated children's expressed emotional valence and arousal, and provided a discrete emotion label for each child.ResultsEmotional valence was positively associated with children's change in chest height and chest expansion: children with more upright upper-body postures were rated as expressing a more positive emotional valence whereas the relation between emotional arousal and changes in body posture was weak.DiscussionThese data add to existing evidence that changes in body posture reliably reflect emotional valence. They thus provide an empirical foundation to conduct research on children's spontaneously expressed emotional valence using the automated and efficient tool of body posture analysis.